Application of Collision Detection in Arjuna's Adventure Game - Pajar Pahrudin; Siti Lailiyah; Dicky Ary Setiawan (Politeknik Pertanian Negeri Samarinda, 2023)
This research makes how to build a 2 dimensional game with the theme of a young man named Arjun who is on the battlefield and is attacked by